2011
DOI: 10.1017/s1368980011002588
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil, an essential component of the Mediterranean diet, and breast cancer

Abstract: Objective: The Mediterranean diet has been related to a lower risk of some chronic diseases, including cancer. We aim to gain insight into the effects of the main source of fat of this diet on breast cancer, the most common type of malignancy in women. Design: Data from sixteen experimental series analysing the effects of dietary lipids on mammary carcinogenesis in an animal model, in the context of the international literature on the Mediterranean diet, olive oil and breast cancer risk. Setting: Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 69 publications
0
57
0
2
Order By: Relevance
“…Several studies have demonstrated the importance of maintaining beneficial lifestyle choices throughout an individual's lifetime to reduce breast cancer risk (Bernstein et al, 1994;Hilakivi-Clarke et al, 2010;Cabanes et al, 2011;Escrich et al, 2011;Lynch et al, 2011;Kark et al, 2012). One possible explanation for this is that the initial accumulation of driver mutations which have the potential to ultimately lead to malignancy, occur in young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the importance of maintaining beneficial lifestyle choices throughout an individual's lifetime to reduce breast cancer risk (Bernstein et al, 1994;Hilakivi-Clarke et al, 2010;Cabanes et al, 2011;Escrich et al, 2011;Lynch et al, 2011;Kark et al, 2012). One possible explanation for this is that the initial accumulation of driver mutations which have the potential to ultimately lead to malignancy, occur in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Escrich et al (2011) determined that breast cancer-induced mice that were fed a diet rich in OO showed a slight protective effect over mice that were fed a high-corn diet. Additionally, the tumors in mice fed with an OO-rich diet were less aggressive, compared to controls (Escrich et al, 2011). Furthermore, OO led to modifications in the tumors which corresponded with lower proliferation, higher apoptosis and lower DNA damage, compared to control tumors.…”
Section: 2207 Mechanics Behind Breast Cancer Prevention -Focus On Obmentioning
confidence: 99%
“…Similarly, in another report including both human and animal studies, diets rich in extra virgin olive oil (EVOO) were found to exert a negative modulatory effect on experimental breast cancer. In addition, EVOO was shown to induce different molecular changes in tumors, such as in the composition of cell membranes, activity of signaling proteins, and gene expression [38].…”
Section: Components Of the Mediterranean Diet And Breast Cancer Risk:mentioning
confidence: 99%
“…In fact, in the Mediterranean diet, olive oil is the principal source of dietary fat, so that there is a high polyunsaturated fatty acid to saturated fatty acid intake ratio. This favorable fatty acid ratio helps maintain a healthy body weight, which is protective with regards to breast carcinogenesis [38]. In addition, EVOO alters the morphology and molecular characteristics of tumors, such as cell membrane composition, signaling protein activity, and gene expression [38], in a way that suggests that it may also have protective effects.…”
Section: The Protective Effect Of the Mediterranean Diet: Mechanisticmentioning
confidence: 99%
“…Olive oil consumption is associated with many health benefits, including protective effects against cardiovascular diseases (Covas, 2007), cognitive decline (Berr et al, 2009) and possibly breast cancer (Escrich, Moral, & Solanas, 2011). The olive oil extraction process, however, involves the generation of large amounts of olive mill wastewater (OMWW), a by-product that constitutes serious environmental problem in the Mediterranean region, due to its high polluting load.…”
Section: Introductionmentioning
confidence: 99%